The Black Church and Hip Hop Culture : Toward Bridging the Generational Divide. - Price, Emmett G., III (African American cultural theory and heritage., 2011)
In this collection of provocative essays, leading thinkers, preachers, and scholars from around the country challenge both the Black church and the hip-hop generation to realize their shared responsibilities to one another and to the greater society.